NALISIS DAMPAK INFLASI, PDRB DAN PERKEMBANGAN UPAH MINIMUM REGIONAL TERHADAP INDEKS PEMBANGUNAN MANUSIA MASYARAKAT DI PROVINSI ACEH - Zainuddin Zainuddin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2015)
This study aims to examine the independent influence, namely inflation, GRDP, and UMR development in Aceh province on the dependent, namely the Human Development Index (HDI) from 2008 to 2013. That together there is an independent influence on HDI. And the independent ability to explain the dependent is 92.94%. The data in this study came from the Aceh Province Central Statistics Agency which was secondary data. The implication of the results of this study is that the parties can put emphasis on what sectors should be done to increase the Human Development Index in Aceh Province.